Instrumentarium fletowe we Lwowie w XIX w. - Karpiak, Andrij (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
During the 19th century, the structure of the flute underwent significant and inevitable changes. Hundreds of famous musical masters devoted their lives to adapting the instrument to the new aesthetic needs of the Romantic era. The role and sound quality of the flute underwent a significant rethinking. Therefore, the inventors’ search was reflected in the external and internal structure, on the attachment of superstructures, on the material from which the samples were made, etc. For several decades, the flute gets a completely new look and structure. Along with the change of the instrument, the change of the system of teaching and performance on the flute begins. The first years after Theobald Böhm’s reform were most clearly and convincingly capable of reflecting the shock state of the industry’s leading specialists, their mostly feverish efforts to reject, deny, glorify, use, „modernizeˮ or calmly accept the realities of the new professional life. So far, little attention has been paid in scientific research to the specifics of familiarization and the initial stages of mastering the newest tools in the provincial centers of Europe. Their experience can provide unusual and original facts for the analysis of individual phases of the professional crisis provoked by the reform and help form a holistic picture of the phenomenal event. The Lviv example vividly demonstrates, on the one hand, the original manifestations of the attitude towards the Munich sensation in the professional and amateur flute world and, on the other hand, some general trends for the process, refracted through the prism of Galician consciousness and mentality. The research uses information and facts that are made public for the first time.